XANTHOGRANULOMATOUS PYELONEPHRITIS AND DIAGNOSTIC APPROACH: A CASE REPORT - Veličković, Filip; Vlajković, Marina; Stević, Miloš; Veličković, Sanja; Janković Veličković, Ljubinka (Acta medicae Medianae, 2023)
Xanthogranulomatous pyelonephritis (XGPN) is an uncommon chronic granulomatous process that can result in significant destruction of renal parenchyma and propagation of inflammation into adjacent pararenal tissues. The presented patient had xanthogranulomatous inflammation of renal pelvis, peri- and paranephritic tissue, with formation of a large tumor-like mass which was in close relation to the base of urinary bladder. The findings of pathognomonic foamy macrophages and multinucleated giant cells showing diffuse positivity for CD68 confirmed the precise diagnosis. Having in mind that XGPN can mimic various clinically and pathologically benign and malignant conditions, a multidisciplinary diagnostic approach is required. Sometimes, careful clinical, imaging, nuclear and histopathological examinations are necessary to determine the type and degree of renal damage, which will dictate surgical approach, especially if nephrectomy is not planned.
Keywords: xanthogranulomatous pyelonephritis, diagnostic approach, histopathology